Single channel atmospheric pressure transporting plasma and plasma stream demultiplexing: physical characterization and application to E. coli bacteria inactivation. (13th July 2017) - Valinataj Omran, A; Sohbatzadeh, F; Siadati, S N; Hosseinzadeh Colagar, A; Akishev, Y; Arefi-Khonsari, F
Abstract: In this article, we developed transporting plasma sources that operate at atmospheric pressure. The effect of electrode configuration on plasma transporting was investigated. In order to increase the transporting plasma cross-section, we converted a plasma stream into four plasma channels by a cylindrical housing. Electron excitation and rotational temperatures were estimated using optical emission spectroscopy. Furthermore, the electrical and temporal characteristics of the plasma, discharge power and charge deposition on the target were investigated. The propagation characteristics of single and multi-channel transporting plasma were compared with the same cross-sectional area. Two configurations for multi-channels were designed for this purpose. Escherichia coli bacteria were exposed to the single and multi-channel transporting discharge for different time durations. After exposure, the results indicated that the inactivation zones were significantly increased by a multi-channel transporting plasma. Finally, E. coli inactivation by those plasma apparatuses was compared with that of several standard antimicrobial test discs such as Gentamicin, Tetracycline, Amoxicillin and Cefixime.